1997
DOI: 10.1088/0953-4075/30/9/019
|View full text |Cite
|
Sign up to set email alerts
|

Ionization - excitation of helium by fast protons and antiprotons

Abstract: The process of simultaneous ionization and excitation of helium by protons and antiprotons is investigated. Total and single differential cross sections for the ionization - excitation process and ionization - excitation probabilities versus the impact parameter are calculated by perturbation theory through the second order in the interaction potential. In the present calculations only the on-energy shell transitions are taken into account. The helium electron wavefunctions for the initial and final states ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Experimental investigations on the double ionization and the ionization-excitation for helium [6,7] and for the hydrogen molecule [24] showed that cross sections for negative projectiles are typically higher than those for positive projectiles with equal velocity over a wide velocity range. Theoretical calculations, however, suggest that for some two-electron transitions in helium-where no experimental data are available-this should not be always the case [25,26]. It therefore seems that for inner-shell excitations of lithium also, the sign of the interference contribution to the cross section depends on the final excited state.…”
Section: Scmentioning
confidence: 99%
“…Experimental investigations on the double ionization and the ionization-excitation for helium [6,7] and for the hydrogen molecule [24] showed that cross sections for negative projectiles are typically higher than those for positive projectiles with equal velocity over a wide velocity range. Theoretical calculations, however, suggest that for some two-electron transitions in helium-where no experimental data are available-this should not be always the case [25,26]. It therefore seems that for inner-shell excitations of lithium also, the sign of the interference contribution to the cross section depends on the final excited state.…”
Section: Scmentioning
confidence: 99%
“…The results of these calculations do not agree with each other, and all underestimate the experimental data [24±28]. Excepting our previous work [22] for the excitation of the 2p state, and Sidorovich [23] for the excitation of the 2s state, nobody has made an attempt to compare theoretical cross sections for same velocity positive and negative projectiles, the other calculations being only for electrons. Experimental data show the same interesting feature as for the double ionization: cross sections for electrons are obtained to be higher than for equivelocity proton projectiles in a wide velocity range.…”
Section: Introductionmentioning
confidence: 83%
“…For the ionization-excitation of the helium, calculations have been made by Rudge [19], Raeker et al [20], Franz and Altick [21], Nagy et al [22], Sidorovich [23]. The results of these calculations do not agree with each other, and all underestimate the experimental data [24±28].…”
Section: Introductionmentioning
confidence: 99%
“…1-2 These many-body aspects of atomic collision processes are associated with electron-electron correlations and other few-body dynamical phenomena that supercede independent-particle models. Most experiments have focused on two-electron mechanisms in helium, since this is the simplest target containing more than one electron, and it is therefore ideally suited for achieving a better theoretical understanding of the few-body problem [3][4][5][6][7][8][9][10][11] that is likely to be useful for the description of other complex systems, e.g. the dynamic behavior of atoms in molecules.…”
Section: Introductionmentioning
confidence: 99%